2015
DOI: 10.1016/j.ultramic.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser energy and wavelength on the analysis of LiFePO4 using laser assisted atom probe tomography

Abstract: The effects of laser wavelength (355 nm and 532 nm) and laser pulse energy on the quantitative analysis of LiFePO₄ by atom probe tomography are considered. A systematic investigation of ultraviolet (UV, 355 nm) and green (532 nm) laser assisted field evaporation has revealed distinctly different behaviors. With the use of a UV laser, the major issue was identified as the preferential loss of oxygen (up to 10 at%) while other elements (Li, Fe and P) were observed to be close to nominal ratios. Lowering the lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 42 publications
5
85
0
6
Order By: Relevance
“…Additionally,peaks for molecules of Mn andOwith different charge states are found, as typically observed for oxides. [18,19,[30][31][32][33] Theh ydrogen assigned to the peaks at m/z = 1, 2, and 3amu most likely stems from residual gas in the chamber, which is field ionized at the sample apex and does not originate from the analyzed material itself. [34,35] At m/z = 69 amu, as ignal from Ga is visible in the overall mass spectrum.…”
Section: Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally,peaks for molecules of Mn andOwith different charge states are found, as typically observed for oxides. [18,19,[30][31][32][33] Theh ydrogen assigned to the peaks at m/z = 1, 2, and 3amu most likely stems from residual gas in the chamber, which is field ionized at the sample apex and does not originate from the analyzed material itself. [34,35] At m/z = 69 amu, as ignal from Ga is visible in the overall mass spectrum.…”
Section: Compositionmentioning
confidence: 99%
“…19 Co 0.04 Al 0.01 Mg 0.01 O 0. 49 , [17] LiFePO 4 , [18] and layered Li 1.2 Ni 0.2 Mn 0.6 O 2 ; [19] these studies have shown the ability and benefit of APT for characterizationo ft hese materials,b ut interpretation of the results in view of Li-ion batteries is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although high laser pulse energy generally results in high success yield, better MRP, and low background, extreme high energy leads to surface migration, complex ion generation, and nonuniform spatial evaporation behavior. The stoichiometry deficiency observed in APT analyses of nitrides and oxide at high laser pulse energy is well known (Devaraj et al, 2013;Kinno et al, 2014;Santhangopalan et al, 2015). For example, in the case of GaN, at the lowest laser energies, the apparent composition is nitrogen-rich, while higher laser energies results in gallium-rich (i.e., nitrogen-deficient) (Gu et al, 2013;Riley et al, 2014;Sanford et al, 2014).…”
Section: Optimization Of Experimental Parametersmentioning
confidence: 99%
“…While this process is relatively well understood for most conducting materials, especially metallic systems [12], the field evaporation process is not always well controlled for insulating materials [13], leading to artifacts in the measured stoichiometry [14][15][16][17][18][19]. These can be exacerbated by the presence of a laser used to thermally assist evaporation for oxides and other materials with limited electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%